2020
DOI: 10.3390/genes11091078
|View full text |Cite
|
Sign up to set email alerts
|

Global Profiling of Dynamic Alternative Splicing Modulation in Arabidopsis Root upon Ralstonia solanacearum Infection

Abstract: Alternative splicing (AS) is an important mechanism by which eukaryotes regulate transcription and protein diversity. The dynamic changes in AS that occur on a genome-wide scale during interactions between plant roots and pathogens remain unknown. Here, we used the interaction between Arabidopsis and Ralstonia solanacearum as a model to explore the AS changes that take place during the response of roots to infection by means of high-throughput RNA-sequencing. We showed that dynamic changes in AS occur much ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…AS events can provide a novel strategy for plant response to virus stresses. AS isoforms can be produced in plants to enhance their transcriptome plasticity and pathogen resistance, helping Brachypodium distachyon defend against the Panicum mosaic virus [ 30 ], wheat cope against powdery mildew [ 31 ], and Arabidopsis against Ralstonia solanacearum [ 50 ]. However, it has not been explored whether AS is involved in maize resistance to various viral infections, except that previous studies showed that maize resistance to MRDD is regulated by many genes that all contribute to overall resistance [ 10 , 29 ] and that Helitron insertion of ZmGDIα ( ZmGDIα -hel) AS events was found to reduce the disease severity index by 30%, which makes it a major MRDD resistance gene [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AS events can provide a novel strategy for plant response to virus stresses. AS isoforms can be produced in plants to enhance their transcriptome plasticity and pathogen resistance, helping Brachypodium distachyon defend against the Panicum mosaic virus [ 30 ], wheat cope against powdery mildew [ 31 ], and Arabidopsis against Ralstonia solanacearum [ 50 ]. However, it has not been explored whether AS is involved in maize resistance to various viral infections, except that previous studies showed that maize resistance to MRDD is regulated by many genes that all contribute to overall resistance [ 10 , 29 ] and that Helitron insertion of ZmGDIα ( ZmGDIα -hel) AS events was found to reduce the disease severity index by 30%, which makes it a major MRDD resistance gene [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This emphasizes that mRNA changes at the transcriptional and post-transcriptional levels can provide a better understanding of stress and development. A previous study demonstrated that only 45 genes overlapped between DEGs and DSGs during the Arabidopsis response to R. solanacearum infection [ 50 ]. Similarly, in maize, 23 genes that overlapped between DSGs and DEGs were identified at 3.0 DAI, whereas RT-PCR was used to verify the predicted AS pattern ( Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…As invaluable and diversi ed posttranscriptional regulation mechanisms in higher eukaryotes, AS events play a crucial role in the life course of plants, including owering induction, circadian rhythms, and stress resistance; in turn, terpenoid synthesis and accumulation are often associated with stress resistance, and terpenoid biosynthetic genes are regulated by AS events (Fig. 3 c) [50][51][52]. HMGCS and HMGCR were identi ed to undergo AS events in the leaves of Ginkgo biloba at different stages of development, and HMGCR is a key enzyme in the MVA upstream pathway of ginsenoside biosynthesis [24] [53].…”
Section: Degs In Ginseng With Different Growth Yearsmentioning
confidence: 99%
“…Recently, alternative splicing (AS) emerged as one of the key regulatory mechanisms in the eukaryotic system ( Wang S. et al, 2022 ; Wright et al, 2022 ). AS plays a significant role in the development and response to biotic and abiotic stressors in plants and therefore provides key revenue to exploit and increase rice production ( Calixto et al, 2018 ; Filichkin et al, 2018 ; James et al, 2018 ; Laloum et al, 2018 ; Zhang G. et al, 2019 ; Dantas et al, 2019 ; Qin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show a massive and rapid AS change that governs the physiological and survival response of plants in response to low temperatures ( James et al, 2012 ; Calixto et al, 2018 ; James et al, 2018 ). AS regulations are likely also involved in responses to biotic stresses ( Zhang H. et al, 2019 ; Qin et al, 2020 ). In the O. sativa indica variety, it was found that the OsGBF1 splice variant is upregulated upon salinity stress ( Ashwini et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%